2018
DOI: 10.3390/v10110617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Staphylococcus aureus Bacteriophage K on Expression of Cytokines and Activation Markers by Human Dendritic Cells In Vitro

Abstract: A potential concern with bacteriophage (phage) therapeutics is a host-versus-phage response in which the immune system may neutralize or destroy phage particles and thus impair therapeutic efficacy, or a strong inflammatory response to repeated phage exposure might endanger the patient. Current literature is discrepant with regard to the nature and magnitude of innate and adaptive immune response to phages. The purpose of this work was to study the potential effects of Staphylococcus aureus phage K on the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
2
7
0
2
Order By: Relevance
“…No significant effect of bacteriophage T4 on the production of cytokines IL-1α, IL-6, IL-12, and TNF-α, as well as on the expression of MHC class II, CD40, CD86, and CD80 was observed [9]. Similar results were obtained by Freyerberger et al [59] who tested whether bacteriophage K affects cytokine expression and activation of human dendritic cell markers. They showed that bacteriophage K had little or no effect on the production of anti-and pro-inflammatory cytokines and the expression of MHC-I and CD80/CD86 proteins [59].…”
Section: Dendritic Cellssupporting
confidence: 81%
“…No significant effect of bacteriophage T4 on the production of cytokines IL-1α, IL-6, IL-12, and TNF-α, as well as on the expression of MHC class II, CD40, CD86, and CD80 was observed [9]. Similar results were obtained by Freyerberger et al [59] who tested whether bacteriophage K affects cytokine expression and activation of human dendritic cell markers. They showed that bacteriophage K had little or no effect on the production of anti-and pro-inflammatory cytokines and the expression of MHC-I and CD80/CD86 proteins [59].…”
Section: Dendritic Cellssupporting
confidence: 81%
“…113 Similarly, certain staphylococcal and pseudomonal phages induce proinflammatory cytokines, such as IL-6 and IL-1b, in murine dendritic cells, 113 whereas other staphylococcal phages did not elicit human dendritic cell cytokine expression. 114 Together, data suggest that immune responses are phage strain dependent.…”
Section: Drug-related Problemsmentioning
confidence: 99%
“…A potential concern of this strategy is that in some patients it may provoke a host-versus-phage inflammatory immune response. This may result in phage neutralization and thereby impair therapeutic efficacy [37]. Thus, any clinical trial to test the suitability of this phage will be diligent to this possibility.…”
Section: Other Treatmentsmentioning
confidence: 99%